Pocket Medicine : The Massachusetts General Hospital Handbook of Internal Medicine - Sabatine, Marc S. (Wolters Kluwer, 2021)
It provides up-to-date, dependable guidance on the internal medicine information needed to make an accurate diagnosis and develop a treatment plan. Compiled by residents and attending physicians at Massachusetts General Hospital. Easy access to essential information on the most common disorders in cardiology, pulmonary medicine, gastroenterology, nephrology, hematology-oncology, infectious diseases, endocrinology, rheumatology, and neurology.